2009
DOI: 10.3748/wjg.15.4234
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, predictors, and clinical consequences of medical adherence in IBD: How to improve it?

Abstract: Inflammatory bowel diseases (IBD) are chronic diseases with a relapsing-remitting disease course necessitating lifelong treatment. However, non-adherence has been reported in over 40% of patients, especially those in remission taking maintenance therapies for IBD. The economical impact of non-adherence to medical therapy including absenteeism, hospitalization risk, and the health care costs in chronic conditions, is enormous. The causes of medication non-adherence are complex, where the patient-doctor relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
56
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 36 publications
3
56
0
2
Order By: Relevance
“…6,7 This finding confirms the problem of medication nonadherence in UC patients in the United States. Oral 5-ASA medication use 21 analyzed a large U.S. pharmacy data file to examine persistency with oral 5-ASA therapy in UC patients.…”
Section: ■■ Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…6,7 This finding confirms the problem of medication nonadherence in UC patients in the United States. Oral 5-ASA medication use 21 analyzed a large U.S. pharmacy data file to examine persistency with oral 5-ASA therapy in UC patients.…”
Section: ■■ Discussionsupporting
confidence: 68%
“…7,13,[16][17][18]21,26,27 Although a few studies reported that daily dose regimen and formulation do not significantly impact adherence, 7,13 2 current studies using patient surveys revealed that frequent dosing and pill burden were important factors for nonadherence. 16,26 Similarly, 2 patterns varied among patients initiated on different 5-ASA medications.…”
Section: ■■ Discussionmentioning
confidence: 94%
See 3 more Smart Citations